A construção e estruturação do território comercial no bairro Alecrim Natal/RN - Silva, Andria Carla Araujo da (2011)
The study done has as objective the comprehension of the constructed territorial spaces through the commercial perspective, because it is a social practice which enables the dynamic of the space and the appearing of territories. Related to the territory, we emphasized the interest for the idea of used territory treated by Milton Santos, because we agreed with him believing that is the use of the territory which warrants its legitimacy. Then, the spatial dimension chose concentrates itself into the district of Alecrim, localized at the east zone of Natal/RN, where it is recognized by its strong commercial dynamic which was built during years, facing some events which happened in the context of the city. However, this dynamic counts with a hard dichotomy which involves as the considered by the State formal activities, as the informal one. About the commerce of the district, it has characteristics into its activities whose make him to be considered popular, as by the existing products, as by the strong presence of informal workers that constitutes the district s landscape. The informal workers practice expresses one of the multiples constructed alternative territorialities. We believe that this fact has direct relation with the growing process of the exclusion from the formal jobs market. Still talking about the spatial dimension, this real example of the Alecrim district shows how the techniques changes, together with the capitalism process, may influence one entire spatial dynamic across years, involving many agents, since the transient people from somewhere, until the State. Shall the Geography understand the multiple forms from the space, face to the relations that occur into it and also how new territories have been built